“Foreign languages” department teacher, - Shadmanbekova, Shadmanbekova (Журнал иностранных языков и лингвистики, 2021)
In the era of the rapid and increasing economic globalization the necessity of teaching Business English cannot be disputed. The paper addresses the basic concepts of Business English (BE), emphasizing the importance of the learner’s needs, i.e. usage of English in a business setting. The focus is also placed on the main topics covered in BE courses, skill areas and lesson formats. The teaching of BE is regarded through the necessary context of English for Specific Purposes (ESP), whose part it doubtlessly is. Moreover, the paper tackles the origins and difficulties one encounters when trying to define the very concepts of both ESP and BE.